Parent‐implemented treatment for automatically maintained stereotypy. (15th August 2019) - Gerow, Stephanie; Rivera, Gabby; Akers, Jessica S.; Kirkpatrick, Marie; Radhakrishnan, Supriya
Abstract : Automatically maintained stereotypy is common among children with autism spectrum disorder. The purpose of this study was to evaluate the effect of a multicomponent parent‐implemented intervention on the reduction of motor stereotypy for a child with autism. A 2‐year‐old child and her father participated in this study. The effect of a parent‐implemented intervention was evaluated using an alternating treatment design. The results indicated that the parent‐implemented treatment package including differential reinforcement, response blocking, and a competing stimulus decreased automatically maintained motor stereotypy.